An Investigation of the Inclusion of Decoloniality in the Objectives of the National Library of South Africa s (NLSA s) Digitisation Programme - Ngcobo, Mhlengi (Library and Information Studies Centre (LISC), 2024)
Decoloniality is a critical issue in South Africa, necessitating action in universities, learning curricula, libraries, and archives, and should not be confused with transformation. In this study, the researcher investigates the inclusion of decoloniality in the objectives of the National Library of South Africa's digitisation programme. A preliminary review of digitisation documents in the National Library of South Africa (NLSA) showed that decoloniality is never explicitly mentioned. The study employed a sequential mixed method, collecting data through documents, questionnaires, and focus group discussions, employing a data triangulation design for flexibility, and evaluating relevant literature and respondents' comments. Participants in this study were comprised of NLSA employees who participated in the digitisation project. This study used a census of 15 library professionals chosen for their ability to provide the most information on the subject. This study confirms that decoloniality is not explicitly mentioned in the NLSA's digitisation documents. The NLSA's digitisation policy is devoid of decolonial strategy plans. According to the findings, research participants did not have a clear understanding of the concept of decoloniality as it relates to the NLSA's digitisation programme. Furthermore, the findings revealed that the NLSA is doing nothing to address decoloniality specifically. The study also revealed challenges related to a lack of funding for digitisation projects, such as a lack of human resources. The findings could not be extrapolated to other South African libraries because this study was limited to the NLSA, and had a small sample size. However, this study's results could be useful to other libraries in the country. The researcher recommends that similar studies for other South African libraries be conducted.